Characteristics of WLAN Transmission in an Indoor Environment - Cheng, Ee Meng (2006)
This thesis describes the study of a deterministic model for WLAN system in indoor environment. The measurement system consists of a spectrum analyzer and a log-periodic antenna. A computer program has been developed to acquire measured field strength data from the spectrum analyzer by using Agilent VEE and analyzed the data by using MATLAB software. Both line-of-sight (LOS) propagation (empty room or corridor) and non-line-of-sight (NLOS) propagation (furnished room) have been investigated. The measured path losses have been compared with deterministic model, namely Geometrical Optics (GO) and Uniform Theory of Diffraction (UTD) with the aid of image theory. The predicted results show good agreement with measurement data for the NLOS environment with absolute mean error ranging between 1.61 dB and 3.07 dB. However, the multiple reflections (third order of multiple reflections estimated the highest order in all cases) and direct ray condition which estimated significant in Instrumentation Laboratory (periodical structural ground) gave poor result when compared with the measured path losses. A typical mean relative error and absolute mean error of direct ray model was found to be within 55.04 % and 7.47 dB, but was further reduced to less than 7.43 % and 0.69 dB after optimization.